HUMAN SECURITY AND THE CONCEPTUALISATION OF SOUTH AFRICAN DEFENCE: TIME FOR A REAPPRAISAL (The Strategic Review for Southern Africa, 2020)
The article traces the unfolding of the human security agenda as the primary organising framework for constructing the security outlook of the South African military. Questions are raised about the utility of human security as a conceptual basis for thinking about and the construction of defence. Human security is historically contextualised within the security conceptualisations of the 1990s. Since then, however, various geo-strategic changes in the world necessitated a return to a more traditional outlook on security and strategy. This reality was also increasingly visible in South Africa's foreign policy approaches and, more specifically, the employment of its armed forces in Africa. The article concludes by arguing, firstly, that the South African armed forces did not at any time critically question how a military should be organised, trained, and equipped for human security operations and, secondly, that the South African National Defence Force never questioned its own operational deployments through the human security perspective.